Efektivitas Hand Washing Adventure Game terhadap Pengetahuan Cuci Tangan pada Anak Sekolah di SDN Sukorejo Lamongan - Suhariyati Suhariyati; Muhammad Afif Misbahul Ulum; Abdul Majid (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Insufficient knowledge of proper handwashing practices among school-age children may contribute to the increased transmission of infectious diseases. Conventional health education approaches are often unable to maintain students’ attention and active participation, creating a need for more engaging and interactive learning media. This study investigated the effect of the Hand Washing Adventure Game on handwashing knowledge among fifth- and sixth-grade students at SDN Sukorejo, Lamongan. A pre-experimental study with a one-group pretest–posttest design was conducted among 70 students selected through total sampling. Knowledge data were obtained using a structured questionnaire administered before and after the intervention. The data were subsequently analyzed using the Wilcoxon test. The analysis demonstrated a statistically significant improvement in students’ knowledge following the intervention (p = 0.001). The median knowledge score increased from 9 before the intervention to 19 after its implementation. These results indicate that the Hand Washing Adventure Game has potential as an interactive educational medium for improving children’s knowledge of correct handwashing practices. The use of digital educational media should therefore be considered in school-based health promotion programs, while future studies are needed to assess whether the improvement in knowledge is sustained and translated into long-term behavioral changes.